SIMULACION NUMERICA DE LLUVIAS EN EL NORTE DEL PERU - Carrillo, Mauricio (2006)
Extreme rains have been observed in the north of Peru, the impact of these rains over the present infrastructure in the cities is important, this due to the high vulnerability of the zone. The events happen mainly in summer. Therefore, fourteen cases of extreme rain have been selected, those that registered during the December and March of 2001 and 2002. In the present research an evaluation of the numerical rain simulation is made in north of Peru. Use a regional model atmospheric call RAMS (Regional Atmosphere Modeling System). It has been implemented in the North zone of Peru using the nesting technique to reduce the resolution. The evaluation of the rain simulation is made measuring the correlation between registered rains and the simulated ones by the model RAMS. The results show a greater correlation for the high river basin, an intermediate value of correlation for the average river basin, and the smaller values of correlation are observed in the low zone of the river basin. These values for the high, intermediate and low river basin are: 0.49, 0,44, and 0,15 respectively. Although these values are apparently low, has appeared values of correlation of 0,90 for the low river basin of the river basin, when simulating the entire extreme rain event. Also values of 0,94 correlations were observed in the high part of the river basin. Some explanations of the low values of correlation, as well as some measures of improvement in the systems of data acquisition are mentioned.